Rediscovering values : coming to terms with Postmodernism - Curtler, Hugh Mercer (Armonk, N.Y. : M.E. Sharpe, 1997)
This book is not a defense of "family values," but a plea to reorient our thinking, turn our attention away from ourselves, and wake up to the world and others that surround and sustain us, and at times threaten us as well. Curtler argues that the objective ground of values is to be found in the way they command our approval, regardless of cultural and personal tastes. Values, as they are conceived here, exist in the common world, and emerge and are experienced in varying social contexts. In the end, it is these values that provide a common ground between postmodern thinkers and their critics and ought properly to be the focus of educational theory.
This book doesn't simply take others to task; it does present a new and interesting theory of valuation, and it speaks in a direct and non-technical way to the reader who is alarmed by the decline of values in all aspects of modern life. It offers not only a strong frontal attack on the defenders of relativity at any cost, but also a well-argued case for the objectivity of values in ethics, literature, and art.
Ch. 1. Inverted Consciousness and the Eclipse of Values -- Ch. 2. The Postmodern Challenge -- Ch. 3. The Rejection of Values -- Ch. 4. What Are Values? -- Ch. 5. Values in the Arts -- Ch. 6. Greatness in Literature -- Ch. 7. Values and the Great Conversation -- Postscript. In Defense of Values.
Includes bibliographical references (p. 169-173) and index.
Keywords: Postmodernism (Literature); Values in literature